152k views
4 votes
Let f(x) = 2x - 1 and g(x) = x^2 + 3x +4

Let f(x) = 2x - 1 and g(x) = x^2 + 3x +4-example-1

1 Answer

0 votes

f(-3)=-7

1) To evaluate a function is to plug one value for x, and find the corresponding f(x) value.

2) Since f(x)= 2x-1 we can evaluate f(-3) this way:


\begin{gathered} f\mleft(-3\mright)=2\mleft(-3\mright)-1 \\ f(-3)=-6-1 \\ f(-3)=-7 \end{gathered}

3) So as we can see when we plug x=-3 we have -7 as the corresponding value.

And that is the answer

User Sheelpriy
by
5.2k points